Measuring customer experience in service: A systematic review. Issue 11 (10th September 2019) - Bueno, Eduardo Veiga; Weber, Tiziana Brenner Beauchamp; Bomfim, Emerson Luiz; Kato, Heitor Takashi
ABSTRACT: The aim of this systematic review is to identify how customer experience in the service sector has been measured in relevant publications in the marketing field. A sample of 33 papers was collected from two electronic databases—the Web of Science (Thomson Reuters) and Scopus (Elsevier)—covering a large number of publications. After analyzing the articles and reviewing the customer experience literature, the following are our main contributions: (i) clarification of the concepts that appear in the literature review of customer experience in the service sector; (ii) classification of the variables, scales, and constructs related to customer experience in service; (iii) demonstration of the service experience as the preponderant construct that is used to measure customer experience in service; and (iv) proposal of a new dimension—the concept of 'pre-experience'—to measure customer experience in service. These contributions can provide a more solid basis for measuring customer experience in service.